Μigration, precarity and the gender violence of domesticity and care - Kambouri, Nelli (The Greek Review of Social Research, 2013)
The paper discusses migration, precarity and gender violence in the context of domestic and care work arguing that gender violence can be best conceptualized and understood from the theoretical perspective of precarity. Precarity becomes from this perspective a double-edged concept describing both the precariousness of life and the forms of escape that may emerge from it. This perspective is contrasted to the dominant anchoring of migration and gender violence to anti- and countertrafficking discourses that silence the agency of migrants in general and migrant women in particular. Taking as its starting point the narrative of a migrant woman from Zimbabwe living as a domestic and care worker in Greece, the paper focuses on precarity as it is produced in the seemingly “private” and feminine spaces of domesticity and care, and highlights the role of networking and acting together as a strategy of actively enacting labour and political rights where they do not exist.